The determination of the relationship between isokinetic leg strengths and agility and speed performance of elite handball players - Aktug, Z. B.; Dündar, A.; Murathan, F.; Iri, R. (Journal of Education and Training Studies, 2018)
The aim of the study is to examine the relationship between isokinetic hamstring and quadriceps muscle strengths and agility and speed performance of elite male handball players. 15 male handball players participated in the study. The isokinetic leg forces of the handball players participating in the study were determined by isokinetic dynamometer, the agility performances by Ilionis and 505 agility test, and the speed performances by photocell. As a result of the analysis, there was no statistically significant relationship between isokinetic dominant and non-dominant leg hamstring and quadriceps peak torque forces and agility and speed performance at 60°s-1 and 400°s-1 angular speeds (p <0.05). As a result, it can be stated that there is no relation between hamstring and quadriceps muscle strength and speed and agility performances of handball players. This may be related to the requirements and physical characteristics of the handball branch (tall height, high weight, high BMI).